CARBON COMPOSITE MATERIAL REINFORCED WITH HIGHLY PURE CARBON FIBER AND ITS PRODUCTION - KONDO TERUHISA; HIRAOKA TOSHIJI; YAMAJI MASATOSHI; OTA NAOTO; SOGABE TOSHIAKI (2000)
PROBLEM TO BE SOLVED: To obtain the subject composite material which can give parts such as a crucible not causing the generation of a defective crystal on the formation of a semiconductor single crystal by controlling the total content of metal impurities and the contents of V and/or Fe among the metal impurities to specific values or less, respectively. SOLUTION: This carbon composite material reinforced with carbon fibers is produced by graphitizing a molded article comprising carbon fibers and a carbon material as a matrix. Therein, the total content of metal impurities is controlled to <=30 ppm as an ash amount by an incineration method, and further controlled to a V (vanadium) content of <=0.12 ppm by an ICP emission spectrometry and/or to a Fe content of <=0.10 ppm by the ICP emission spectrometry. Before the molded article is graphitized and further before the carbon material is charged, the carbon fibers are preferably subjected to a high purity treatment using a halogen gas so as to give an ash content of preferably <=80 ppm by an incineration method. The composite material preferably has a bulk density of 1.35-1.80 g/cm3 after the graphitization, and the carbon fibers are fibers, a woven fabric or yarns. The carbon material is preferably produced from a pitch, phenol or pyrolyzed carbon.